Factorial validity of the organizational health inventory among Omani teachers: Invariance across gender - Aieman Ahmad Al-Omari; Yousef Abdelqader Abu Shindi (Institute of Advanced Engineering and Science, 2022)
This study examined the factor structure of the Organizational Health Inventory (OHI) scale among Omani teachers. There were four factors assumed to represent the OHI (principal influence, academic emphasis, morale, and initiating integrity). Testing the scale reliability was another aim of this study. A random sample (n=458) of Omani teachers was considered. The short version of the scale has 30 items. Exploratory and confirmatory factor analysis was performed on the sample data. The model is good fitted to the data. Across gender, the invariance of the structure was tested, and the parameters of the model were invariant. Consequently, the two genders were compared via multivariate analysis of variance (MANOVA) with gender as an independent variable and subscales. The female teachers were found to more likely show principal influence, academic emphasis, and morale than the male teachers, who instead, were more efficacious than the female teachers in dealing with institutional integrity.